2011
DOI: 10.4254/wjh.v3.i9.228
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoids as potential chemopreventive and therapeutic agents in liver cancer

Abstract: Despite significant advances in medicine, liver cancer, predominantly hepatocellular carcinoma remains a major cause of death in the United States as well as the rest of the world. As limited treatment options are currently available to patients with liver cancer, novel preventive control and effective therapeutic approaches are considered to be reasonable and decisive measures to combat this disease. Several naturally occurring dietary and non-dietary phytochemicals have shown enormous potential in the preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
149
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(153 citation statements)
references
References 180 publications
(301 reference statements)
1
149
1
2
Order By: Relevance
“…The data reported by other authors also showed that these substances are volatile constituents in Euphrasia stricta and E. rostkoviana [Miladinovic et al 2014, Novy et al 2015. The terpene compounds are responsible for the antioxidant, antiviral, antibacterial, and antifungal properties [Thoppil and Bishayee 2011].…”
Section: Discussionmentioning
confidence: 81%
“…The data reported by other authors also showed that these substances are volatile constituents in Euphrasia stricta and E. rostkoviana [Miladinovic et al 2014, Novy et al 2015. The terpene compounds are responsible for the antioxidant, antiviral, antibacterial, and antifungal properties [Thoppil and Bishayee 2011].…”
Section: Discussionmentioning
confidence: 81%
“…Flavonoid also have potency on inhibition of carcinogen metabolic inhibition, antiproliferation, apoptosis induction, antioxidants activity, and angiogenesis inhibition (Ren et al, 2003;Kanadaswami et al, 2005). Terpenoid, such as monoterpene, diterpene, triterpene, tetraterpene, and sesquiterpene, have potency as chemotherapeutic and therapeutic agents to the liver cancer (Thoppil & Bishayee, 2011).…”
Section: Results and Discussion Cytotoxic Activity Of S Plicata Crudmentioning
confidence: 99%
“…Mucus also contain chemical deterrents, as shown for shelled gastropods and nudibranchs which may be attributed to the observed cytotoxic and genotoxic effects. Many of these deterrents are apoptosis, and suppress tumor angiogenesis, invasion and metastasis through regulation of various transcription and growth factors as well as intracellular signaling mechanisms [24]. Lastly, proteins from marine animals such as molluscs have been shown to have cytotoxic effect on several human cancer cell lines [11].…”
Section: Discussionmentioning
confidence: 99%